Effect of the gut microbiome, skin microbiome, plasma metabolome, white blood cells subtype, immune cells, inflammatory proteins, and inflammatory cytokines on asthma: a two-sample Mendelian randomized study and mediation analysis - Guo, Wenqian; Hong, Er; Ma, Han; Wang, Ji; Wang, Qi (Frontiers in Immunology, 2025)
BackgroundAsthma is a chronic inflammatory disorder arising from incompletely understood heterogenic gene–environment interactions. This study aims to investigate causal relationships among gut microbiota, skin microbiota, plasma metabolomics, white blood cells subtype, immune cells, inflammatory proteins, inflammatory cytokines, and asthma.MethodsFirst, two-sample Mendelian randomization analysis was used to identify causal relationships. The summary statistics of 412 gut microbiota traits (N = 7 738), 150 skin microbiota traits (N = 579), 1 400 plasma metabolite traits (N = 8 299), white blood cells subtype counts (N = 746 667), 731 immune cell traits (N = 3 669), 91 circulating inflammatory proteins (N = 14 744), 41 inflammatory cytokine traits (N = 8 293), and asthma traits (N = 244 562) were obtained from publicly available genome-wide association studies. Inverse–variance weighted regression was used as the primary Mendelian randomization method. A series of sensitivity analyses was performed to test the robustness of causal estimates. Subsequently, mediation analysis was performed to identify the pathway from gut or skin microbiota to asthma mediated by plasma metabolites, immune cells, and inflammatory proteins.ResultsMendelian randomization revealed the causal effects of 31 gut bacterial features (abundances of 19 bacterial pathways and 12 microbiota), 10 skin bacterial features, 108 plasma metabolites (81 metabolites and 27 ratios), 81 immune cells, five circulating inflammatory proteins, and three inflammatory cytokines and asthma. Moreover, the mediation analysis results supported the mediating effects of one plasma metabolite, five immunophenotypes, and one inflammatory protein on the gut or skin microbiota in asthma pathogenesis.ConclusionThe findings of this study support a causal relationship among gut microbiota, skin microbiota, plasma metabolites, immune cells, inflammatory proteins, inflammatory cytokines, and asthma. Mediating pathways through which the above factors may affect asthma were proposed. The biomarkers and mediation pathways identified in this work provide new insights into the mechanism of asthma and contribute to its prevention and treatment.